Development and validity of a mentally-passive and mentally-active sedentary time questionnaire in nursing college students - Qi, Meiling; Gao, Yiming; Zhao, Xiangyu; Jones, Cindy; Moyle, Wendy; Shen, Shiyu; Li, Ping (Frontiers in Public Health, 2023)
Objective This study aimed to develop and validate a questionnaire to evaluate nursing college students’ mentally-passive and mentally-active sedentary time (M-PAST) in China. Methods An initial M-PAST questionnaire with mentally-passive and mentally-active sedentary behaviors was developed with content validity undertaken through a consensus panel and pilot test where a convenience sample of six nursing students was recruited to assess the relevance, comprehensiveness, and comprehensibility of the refined questionnaire after expert panelists’ responses. A cross-sectional online survey using a self-reported questionnaire was distributed to nursing students by email and then conducted using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to assess the construct validity of the M-PAST questionnaire and factor structures. Finally, the criterion validity was examined by exploring the associations between the M-PAST and the IPAQ sitting time, psychological distress, and insomnia. Results Eight items regarding learning and leisure were included in the final version of the M-PAST questionnaire. A group of 650 nursing college students in China completed the study. Principal component analysis revealed two factors (i.e., mentally-passive and mentally-active sedentary behaviors), which explained 41.98% of the variance contributing to the questionnaire. The CFA reached the adaptive standard. Cronbach’s α ranged from 0.730 to 0.742. The correlations between M-PAST and IPAQ total sitting time were significant (p < 0.01, r = 0.125–0.396). Mentally-passive sedentary time was associated with psychological distress and insomnia (p < 0.01, r = 0.078–0.163), while no significant associations were found in mentally-active sedentary behaviors. Conclusion and implications for practice The M-PAST questionnaire appears to be a reliable and valid tool that reported both mentally-passive and mentally-active sedentary behaviors in nursing college students in China. However, future studies may need to further examine its validity among international nursing college students. This study further confirmed that mentally-passive sedentary behavior was positively associated with psychological distress and insomnia. Effective strategies are needed to reduce nursing college students’ mentally-passive sedentary time to improve their health and wellbeing in China.